Nigeria federal and state-level governments incorporated biofortification scaling strategies for vitamin A maize and vitamin A cassava - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Federal Ministry procured Vitamin A maize and cassava (VAM/VAC) seeds for input subsidy program; three state governments allocated budgets for VAC stem distribution; Home-Grown School Feeding Program partnership initiated.